FACTORS ASSOCIATED WITH PREVENTIVE BEHAVIORS FOR UNPLANNED PREGNANCY AND SEXUALLY TRANSMITTED DISEASES AMONG HIGH SCHOOL STUDENTS IN MUANG DISTRICT, NAKHON RATCHASIMA PROVINCE - หน่อแก้ว จุน; อุดมพร ธีรยุทธ; ศิลา ศิระวัตร; โพธิพิมพ์ มะลิ; เพชรเลียบ วิทชย; สังวะลี วรารัตน์ (Primary Health Care Journal (Northeastern Edition), 2024)
The objective of this cross-sectional research is to examine the factors associated with the behaviors of unwanted pregnancy prevention and sexually transmitted diseases among high school students in Mueang District, Nakhon Ratchasima Province. The sample group consists of 394 high school students aged between 12 and 18 years. Data collection was conducted using a questionnaire, and the quality was ensured by analyzing the index of questionnaire item congruence with the content, yielding a value of 0.89. Additionally, the reliability of perception variables was assessed using the KR-20 method, resulting in a value of 0.96. The Cronbach’s alpha coefficients for attitude perception variables and behavioral variables were 0.79 and 0.64, respectively. Statistical analysis included descriptive statistics, means, standard deviations, and correlation coefficients. The study found significant correlations (p < .05) between certain factors and behaviors related to unwanted pregnancy prevention and sexually transmitted diseases. These factors include gender, academic performance, and the main occupation of parents. However, perception variables showed no significant correlation with behaviors related to unwanted pregnancy prevention and sexually transmitted diseases. In conclusion, gender, academic performance, parents’ main occupation, and attitudes are significant factors in planning and implementing strategies to change behaviors related to unwanted pregnancy prevention and sexually transmitted diseases among students.